Real-space measurement of the potential distribution inside organic semiconductors - Kemerink, Martijn; Offermans, Peter; Duren, Jeroen Karolus Johannes van; Koenraad, Paulus M.; Janssen, René A. J.; Salemink, Huub W.; Wolter, Joachim H. (Physical review letters, 2002)
We demonstrate that the soft nature of organic semiconductors can be exploited to directly measure the potential distribution inside such an organic layer by scanning-tunneling microscope (STM) based spectroscopy. Keeping the STM feedback system active while reducing the tip-sample bias forces the tip to penetrate the organic layer. From an analysis of the injection and bulk transport processes it follows that the tip height versus bias trace obtained in this way directly reflects the potential distribution in the organic layer.
Gesehen am 16.12.2019